THE MATHEMATICAL JUSTIFICATION OF THE EXTRACTION PLANT ELEMENTS OPERATION - A. M. Medvedev; V. N. Savin; V. I. Shipulin (Современная наука и инновации)
The aim of the research is to optimize the parameters of the extraction plant for the production of C02 extracts. The principle of operation of the extraction unit with a C02 extractor, evaporator, condenser andpulsator is described. A block diagram of the production of C02 extracts is presented. A special feature of the installation is the possibility of using miscella as a solvent. The thermo-physical characteristics of heat exchange processes are calculated without taking into account the influence of local velocities of liquid and gaseous C02 on the boiling and condensation characteristics, taking into account only the volumetric nature of boiling and surface condensation in the conditions of interaction with pipe heat exchange elements. Under the conditions of volumetric boiling of the solvent, the calculation of the evaporator for the separation of the miscella is carried out. The information obtained can be used in the design of gas-liquid installations.